2019
DOI: 10.1002/jum.15003
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and Histopathologic Correlation of Ovarian Cystadenofibromas: Diagnostic Value of the “Shadow Sign”

Abstract: Objectives Cystadenofibromas (CAFs) are rare benign ovarian tumors without a widely accepted ultrasound (US) pattern. They are usually described by as thin‐walled, unilocular or multilocular, and at times septated cysts with scant blood flow and no solid components. We describe a unique US feature, the “shadow sign,” seen in prospectively diagnosed benign CAFs. We also provide the histopathologic basis for this typical US appearance. Methods Ultrasound (US) examinations were performed in our obstetric and gyne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Ovary tumors related to pregnancy are mostly benign; functional ovarian cysts are the most common type of them; however, there are other formations, such as cystic teratomas, cystadenomas, and endometriomas [1]. The real incidence rate of cystadenofibroma is unknown; however, it is relatively rare and can happen in women in the age group 23 to 80 years -mean age of 59 years [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ovary tumors related to pregnancy are mostly benign; functional ovarian cysts are the most common type of them; however, there are other formations, such as cystic teratomas, cystadenomas, and endometriomas [1]. The real incidence rate of cystadenofibroma is unknown; however, it is relatively rare and can happen in women in the age group 23 to 80 years -mean age of 59 years [2].…”
Section: Discussionmentioning
confidence: 99%
“…Most ovary tumors related to pregnancy are benign. Masses identified during pregnancy are rarely malignant, which shows incidence rate of approximately 1-8% [1,2]. However, this is not the only risk associated with adnexal mass during pregnancy; benign masses in the second trimester of pregnancy can lead to complications such as torsion, rupture, and labor obstruction [3,4], which demands thorough and careful monitoring by the obstetrician.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while the cystadenofibroma (Figure S5) displayed a somewhat similar silhouette pattern to that of the BOTs, it lacked blood vessels in the initial 2D microvascular color Doppler image (Figure S5c,d). Also, and unlike the BOTs, cystadenoma and two ovarian malignancies, only the histologically confirmed cystadenofibroma displayed acoustic shadowing 10 . The larger, fluid‐filled inner‐wall structures of serous cystadenomas (Figure S6) should not be confused with the much smaller 1–3‐mm microcysts of BOTs.…”
Section: Figurementioning
confidence: 95%
“…To facilitate the accurate preoperative assessment, Landolfo et al 24 showed that an acoustic shadow behind a papillary projection independently decreased the odds of malignancy. Timor‐Tritsch et al 25 described the “shadow sign” as a pathognomonic characteristic of cystadenofibromas. They showed that cystadenofibromas are usually unilocular (rarely multilocular), and more than 50% have solid inner‐wall fibrotic nodules, which are hyperechoic, avascular, and cast acoustic shadowing 25 .…”
Section: Challenges In Assessing Adnexal Massesmentioning
confidence: 99%
“…Timor‐Tritsch et al 25 described the “shadow sign” as a pathognomonic characteristic of cystadenofibromas. They showed that cystadenofibromas are usually unilocular (rarely multilocular), and more than 50% have solid inner‐wall fibrotic nodules, which are hyperechoic, avascular, and cast acoustic shadowing 25 . This is a reliable sign that can help differentiate cystadenofibromas from borderline ovarian tumors and ovarian malignancies 25,26 (Figure 3).…”
Section: Challenges In Assessing Adnexal Massesmentioning
confidence: 99%